Nursing Management of Ineffective Airway Clearance Through Effective Cough Exercise and Warm Water Ad-ministration in Chronic Obstructive Pulmonary Disease Pa-tients at RSUD Dr. Gondo Suwarno Ungaran - Suci Indah Lestari; Tri Susilo (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic respiratory disorder characterized by per-sistent airflow limitation, excessive mucus production, chronic cough, and difficulty in clearing airway secretions. Ineffective airway clearance is one of the common nursing problems experienced by COPD patients due to increased sputum production and decreased ability to perform effective coughing. This article aims to describe nursing management of ineffective airway clearance through effective cough exercise combined with warm water administration in COPD patients. This study used a descriptive case study approach based on the nursing process, including assessment, nursing diagnosis, intervention, imple-mentation, and evaluation. The case was conducted at RSUD Gondo Suwarno Ungaran involving a COPD patient with ineffective airway clearance problems. Nursing interventions included respiratory monitoring, effective cough training, semi-Fowler positioning, and warm water administration to assist sputum mo-bilization. The results showed improvement in airway clearance, characterized by easier sputum expecto-ration, reduced respiratory discomfort, and improved breathing condition. Effective cough exercise combined with warm water administration can be used as a simple non-pharmacological nursing inter-vention to support airway clearance management in COPD patients.